Mitochondrial DNA leakage triggers inflammation in age-related cardiovascular diseases - Ding, Wanyue; Chen, Jingyu; Zhao, Lei; Wu, Shuang; Chen, Xiaomei; Chen, Hong (Frontiers in Cell and Developmental Biology, 2024)
Mitochondrial dysfunction is one of the hallmarks of cardiovascular aging. The leakage of mitochondrial DNA (mtDNA) is increased in senescent cells, which are resistant to programmed cell death such as apoptosis. Due to its similarity to prokaryotic DNA, mtDNA could be recognized by cellular DNA sensors and trigger innate immune responses, resulting in chronic inflammatory conditions during aging. The mechanisms include cGAS-STING signaling, TLR-9 and inflammasome activation. Mitochondrial quality controls such as mitophagy could prevent mitochondria from triggering harmful inflammatory responses, but when this homeostasis is out of balance, mtDNA-induced inflammation could become pathogenic and contribute to age-related cardiovascular diseases. Here, we summarize recent studies on mechanisms by which mtDNA promotes inflammation and aging-related cardiovascular diseases, and discuss the potential value of mtDNA in early screening and as therapeutic targets.